Altered Development of Prefrontal GABAergic Functions and Anxiety-like Behavior in Adolescent Offspring Induced by Prenatal Stress - Suwaluk A. (2023)
Maternal stress can afflict fetal brain development, putting the offspring at risk of cognitive deficits, including anxiety. The prefrontal cortex (PFC), a protracted maturing region, is notably affected by prenatal stress (PS). However, it remains unclear how PS interferes with the maturation of the GABAergic system, considering its functional adjustment in the PFC during adolescence. The present study thus investigated the long-lasting consequences of PS on the prefrontal GABAergic functions of adolescent offspring. Pregnant Sprague–Dawley rats were divided into controls and the PS group, which underwent restraint stress during the last week of gestation. Male pups from postnatal days (PND) 40–42 were submitted to the elevated plus maze (EPM) test. Proteins essentially involved in GABAergic signaling were then examined in PFC tissues, including the K+-Cl− cotransporter (KCC2), Na+-K+-Cl− cotransporter (NKCC1), α1 and α5 subunits of GABA type A receptors (GABAA receptors), and parvalbumin (PV), along with cAMP response element-binding protein phosphorylation (pCREB), which reacts in the plasticity regulation of PV-positive interneurons. The results revealed that the higher anxiety-like behavior of PS adolescent rats concurred with the significant decreases of the KCC2 and α1 subunits, with PV- and pCREB-lowered levels. The findings suggested that PS disrupts the continuance of PFC maturity by reducing the essential elements of GABAergic functions. These changes likely underlie the anxiety emerging in adolescence, possibly progressing to mental disorders.